TGA-FTIR study on the slow pyrolysis of lignin and cellulose-rich fractions derived from imidazolium-based ionic liquid pre-treatment of sugarcane straw. (15th November 2019) - Halder, Pobitra; Kundu, Sazal; Patel, Savankumar; Parthasarathy, Rajarathinam; Pramanik, Biplob; Paz-Ferreiro, Jorge; Shah, Kalpit
Graphical abstract: Highlights: Disorder of cellulosic H-bonds during pre-treatment developed amorphous Cellulose II. [Emim][OAc] pre-treatment reduced the activation energy of biomass pyrolysis. Presence of amorphous Cellulose II in treated biomass enhanced dehydration reaction. Enhanced dehydration of treated biomass during pyrolysis increased furans yield. Cleavage of β-O-4 bonds of lignin during pre-treatment enhanced phenols yield. Abstract: Slow pyrolysis of regenerated cellulose-rich material ( RCRM ) and recovered lignin produced from imidazolium-based ionic liquid (IL) pre-treatment of sugarcane straw ( SCS ) was investigated employing a Thermogravimetric Analyser (TGA) instrument coupled with a Fourier-Transform Infrared (FTIR) spectroscopy. 1-ethyl-3-methylimidazolium acetate ([Emim][OAc]) pre-treatment of SCS altered the hydrogen bonds of cellulose and produced amorphous Cellulose II structure in RCRM . FTIR spectroscopic analysis of liquid products showed that the IL pre-treatment increased the production of furans from the pyrolysis of RCRM, because the presence of amorphous Cellulose II in RCRM enhanced the dehydration reaction during pyrolysis. Moreover, the recovered lignin from IL pre-treatment enhanced the production of phenol-rich pyrolysis oil due to the cleavage of β-O-4 ether bonds of lignin during pre-treatment. Scanning electron microscope (SEM) analysis indicated highly porous structure of both RCRM and recovered lignin derived biochars. The kinetic analysis using a hybrid approach (a combination of model-fitting and model-free methods) indicated a reduction in the activation energy for both RCRM and recovered lignin pyrolysis. It is concluded that IL pre-treatment of lignocellulosic biomass followed by low-temperature pyrolysis can be an efficient route for biorefinery production.